PECULIAR FEATURES OF GEODESIC VERTICALITY CONTROL OVER AERIAL TOWERS FOR RADIO-RELAY AND CELL COMMUNICATION - M. S. Nesterenok (Наука и техника)
The paper shows that heel determination of modern aerial towers for radio-relay and cell communication of triangle cross-section requires forced unit of temporary observation stations on horizontal symmetry axis of  such objects with the given accuracy. It has been recommended to determine the heel relatively to three support directions with the purpose of proper control over result accuracy